Yeast-based assays for screening 11β-HSD1 inhibitors. Issue 1 (December 2016) - Vanella, Rosario; Callari, Roberta; Weston, Anna; Heider, Harald; Schwab, Markus; Kübler, Eric
Abstract Background Intracellular metabolism of glucocorticoid hormones plays an important role in the pathogenesis of metabolic syndrome and regulates, among many physiological processes, collagen metabolism in skin. At the peripheral level the concentration of active glucocorticoids is mainly regulated by the 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) enzyme, involved in the conversion of cortisone into the biologically active hormone cortisol. Cortisol interacts with the glucocorticoid receptor and regulates the expression of different classes of genes within the nucleus. Due to its implication in glucocorticoid metabolism, the inhibition of 11β-HSD1 activity has become a dominant strategy for the treatment of metabolic syndrome. Moreover, inhibitors of this target enzyme can be used for development of formulations to counteract skin ageing. Here we present the construction of two yeast cell based assays that can be used for the screening of novel 11β-HSD1 inhibitors. Results The yeastSaccharomyces cerevisiae is used as a host organism for the expression of human 11β-HSD1 as well as a genetically encoded assay system that allows intracellular screening of molecules with 11β-HSD1 inhibitory activity. As proof of concept the correlation between 11β-HSD1 inhibition and fluorescent output signals was successfully tested with increasing concentrations of carbenoxolone and tanshinone IIA, two known 11β-HSD1 inhibitors. The first assay detects a decrease in fluorescence upon 11β-HSD1 inhibition, whereas the second assay relies on stabilization of yEGFP upon inhibition of 11β-HSD1, resulting in a positive read-out and thus minimizing the rate of false positives sometimes associated with read-outs based on loss of signals. Specific inhibition of the ABC transporter Pdr5p improves the sensitivity of the assay strains to cortisone concentrations by up to 60 times. Conclusions Our yeast assay strains provide a cost-efficient and easy to handle alternative to other currently available assays for the screening of 11β-HSD1 inhibitors. These assays are designed for an initial fast screening of large numbers of compounds and enable the selection of cell permeable molecules with target inhibitory activity, before proceeding to more advanced selection processes. Moreover, they can be employed in yeast synthetic biology platforms to reconstitute heterologous biosynthetic pathways of drug-relevant scaffolds for simultaneous synthesis and screening of 11β-HSD1 inhibitors at intracellular level.